A survey of the internal oral morphology in larvae of the genus Hylodes Fitzinger, 1826 (Amphibia, Anura, Hylodidae) - Weber, Luiz Norberto; Caramaschi, Ulisses (Zootaxa, 2013)
From the 24 species allocated in the genus Hylodes, 16 have their tadpoles described, which five have information on the oral anatomy. Herein, the internal oral morphology of the tadpoles of H. dactylocinus, H. heyeri, H. aff. lateristrigatus, H. magalhaesi, H. meridionalis, H. phyllodes, H. sazimai, and H. uai is described, along with comparisons among all species in the genus with previously known oral morphology.